Energy in the 21st Century. - Fanchi, John R. (World Scientific, 2010)
Energy may be the most important factor that will influence the shape of society in the 21st century. The cost and availability of energy significantly impacts our quality of life, the health of national economies, the relationships between nations, and the stability of our environment. What kind of energy do we want to use in our future? Will there be enough? What will be the consequences of our decisions? Everyone has a stake in the answers to these questions and the decisions that are being made to provide energy. "Energy in the 21st Century", in its second edition, examines the e.